The Performance of the Ritual of Slawatan and the Influence of a Charismatic Leader - Sarr, Ebrima; Syamsuddin, Sahiron (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2019)
This paper focuses on the the performance of Slawatan and the charismatic leadership of Habib Sheikh as a source of motivation for diverse communities in Central Java. The paper uses ritual and performance theories as the guiding framework. The data-gathering method was derived from participant observation, interviews and discussions. The study argues that the ritual performance of Slawatan follows a systematic process and the charismatic leadership of Habib Sheikh serves as a motivation for different groups. The findings show that the performance of Slawatan is a process that includes the preliminaries, dress code, verses and songs, and the ‘cool-down’ part. They reveal how people from diverse communities see Habib Sheikh as very charismatic. They believe that his leadership qualities and innovations motivate them to attend this form of Islamic ritual performance. This study is part of a growing body of research on the understanding of Islamic ritual as a peaceful event which people from different backgrounds can attend and enjoy religious songs and music, without fear of encountering aggressive teachings and practices. It also contributes to future research on comparable issues.